Diversity and potential of nuisance flies as vectors of gastrointestinal parasitic diseases in traditional markets in Surabaya City - Kurniabudhi , Marek Yohana; Nugroho , Eko Prasetyo; Wahyuningtyas, Puput Ade (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2025)
Nuisance flies are known mechanical vectors capable of transmitting bacterial agents, protozoa, and helminth eggs—particularly Soil-Transmitted Helminths (STH)—from traditional market environments to human food. This study aimed to identify the diversity and distribution of nuisance fly species and to investigate the presence of gastrointestinal parasites in these flies at traditional markets in Surabaya City. Fly samples were collected from five traditional markets and examined using native, sedimentation, and flotation techniques under a microscope. Descriptive statistics were employed to analyze species diversity, relative Abundance, frequency, dominance, and Shannon-Wiener diversity index (H'). The identified species included Chrysomya megacephala, Chrysomya saffranea, Lucilia sp., Musca domestica, and Sarcophaga sp., with M. domestica being the dominant species across all markets. Endoparasitological examination revealed the presence of protozoa and helminth eggs. Entamoeba sp. was consistently detected (100%) in both fly genera, while Isospora sp. oocysts were exclusively found in M. domestica from Wonokusumo Market. Ancylostoma sp. and Toxocara sp. eggs were identified in M. domestica from several markets and in Chrysomya sp. from Kaliwaron LKMK Market. The presence of these parasites is likely due to the flies’ contact with contaminated substrates such as sewage, market waste, animal carcasses, or vegetables. These findings underscore the importance of nuisance fly surveillance, as these insects not only cause discomfort but also act as vectors of zoonotic pathogens posing health risks to animals and humans.